The Dilemmas and Opportunities of Value Investing Paradigms in the Age of Technological Disruption - Gan Weitao (SHS Web of Conferences)
With the widespread adoption of emerging technologies such as the Internet, big data, and artificial intelligence, traditional value investment theories are encountering unprecedented challenges and opportunities. These technologies are reshaping information asymmetry, market efficiency assumptions, and enterprise valuation models. The rapid advancement of digital technology is fundamentally transforming traditional theories and practices of value investing, leading to the emergence of new evaluation frameworks. Therefore, this paper examines how digital technology impacts and reshapes the logic of value creation, systematically analyzing the limitations of value investing in the digital age and proposing three innovative approaches. The study highlights the dual nature of digital technology’s influence on value investing: while it accelerates value discovery, it also introduces potential systemic risks. By providing a cognitive framework for value assessment in the era of technological civilization, this research offers valuable insights for investors, regulators, and academics, addressing the gap in existing theories within the digital context. This framework will enhance the technological adaptability of the capital market, promoting the stability and development of financial markets and lays a robust foundation for future research.